In situ speciation of uranium in treated acid mine drainage using the diffusion gradients in thin films technique (DGT) - Pedrobom, Jorge Henrique [UNESP]; Eismann, Carlos Eduardo [UNESP]; Menegário, Amauri A. [UNESP]; Galhardi, Juliana Aparecida [UNESP]; Luko, Karen Silva [UNESP]; Dourado, Thiago de Araujo [UNESP]; Kiang, Chang Hung [UNESP] (Elsevier, 2017)
The exchange membranes P81 and DE81 and Chelex-100 resin were used to perform in situ speciation of uranium in treated acid mine drainage at the Osamu Utsumi mining site, Poços de Caldas city, Southeast Brazil. To investigate possible chemical modifications in the samples during analysis, the three ligands were deployed in situ and in a laboratory (in lab). The results obtained in situ were also compared to a speciation performed using Visual MINTEQ software. Chelex-100 retained total labile U for a period of up to 48 h. The labile U fraction determined by Chelex 100 ranged from 107 ± 6% to 147 ± 44% in situ and from 115 ± 22% to 191 ± 5% in lab. DE81 retained anionic U species up to 8 h, with labile fractions ranging from 37 ± 2% to 76 ± 3% in situ and 34 ± 12% to 180 ± 17% in lab. P81 exhibited a lower efficiency in retaining U species, with concentrations ranging from 6± 2% to 19± 2% in situ and 3± 2% to 18± 2% in lab. The speciation obtained from MINTEQ suggests that the major U species were UO2OH+, UO2(OH)3−, UO2(OH)2(aq), Ca2UO2(CO3)3(aq), CaUO2(CO3)3 2−, UO2(CO3)2 2−, and UO2(CO3)3 4−. This result is in accordance with the results obtained in situ. Differences concerning speciation and the total and soluble U concentrations were observed between the deployments performed in situ and in the laboratory, indicating that U speciation must be performed in situ.
Keywords: In situ; Multiple DGT devices; Speciation; Treated acid mine drainage; Uranium